Measuring The Motor Ability of Students Participating Vocational Volleyball Extracurricularies in Cilacap District - Kusmiyati Kusmiyati; Dian Imam Saefulah; Slamet Riyadi (Universitas Sebelas Maret, 2022)
Extracurricular activities, especially in the field of sports, are one type of activity outside school hours that can improve the quality of fitness and develop students' motor movements. This research aims to determine the value description and analyze the level of motor skills of students participating in extracurricular volleyball at Darussalam Vocational School, Cilacap Regency. The research subjects were 20 students who were participants in extracurricular volleyball at Darussalam Vocational School, Cilacap Regency. This research is included in the type of non-experimental research with a quantitative approach. The research implementation method was carried out using a descriptive method. To find out a picture of students' motor skills, the Borrow Motor Ability Test test instrument was used. The analysis was carried out by analyzing the mean and standard deviation of the data which had previously been converted into a t-score to equate the units. The research results showed that of all the test items carried out by students participating in extracurricular volleyball at Darussalam Vocational School, Cilacap Regency, there was 1 student who was in the very good category (5%), 5 students in the good category (25%), 9 students in the moderate category ( 45%), 4 students in the poor category (20%), and 1 student in the very poor category (5%). Of all the test items carried out, it can be said that the level of motor skills of students who are members of the volleyball extracurricular at Darussalam Vocational School, Cilacap Regency is classified as in the medium category.